Avaliação da dinâmica dos processos erosivos lineares e sua relação com a evolução do uso da terra - Pinton, Leandro de Godoi [UNESP]; da Cunha, Cenira Maria Lupinacci [UNESP] (My University, 2008)
The development of linear erosion processes is directly related with the environment natural characteristics or with modifications that have occurred on them by the anthropic action. In this context, the present article has as a general objective to evaluate the dynamic of the linear erosion processes and their relations with the evolution of the land use and with the lito-pedologic characteristics of the Cavalheiro hydrographic basin - Analândia, SP. In order to reach such objective, maps of erosive features and land use of several settings were elaborated, besides cartographic representations of the geological and pedological data of the study area. The obtained data were analyzed starting from the principles that concern to the General Systems Theory. Such analysis evidenced the intrinsic bond of the development of linear erosion processes with the several forms of land use and with the natural attributes of the studied area. Therefore, the methodological procedure adopted in this research has been considered as fundamental tool to understand the linear erosion processes dynamic, making it possible to take data of extreme relevance for the planning of the use and occupation of the land.

O desenvolvimento dos processos erosivos lineares está relacionado diretamente com as características naturais do ambiente ou com modificações ocorridas nestas pela ação antrópica. Neste contexto, o presente artigo teve como objetivo geral avaliar a dinâmica dos processos erosivos lineares e as suas relações com a evolução do uso da terra e com as características lito-pedológicas da bacia do Córrego do Cavalheiro – Analândia, SP. A fim de atender tal objetivo, foram elaboradas cartas de feições erosivas e de uso da terra de diversos cenários, além de representações cartográficas dos dados geológicos e pedológicos da área de estudo. Os dados obtidos foram analisados a partir dos princípios que concernem à Teoria Geral dos Sistemas. Tal análise evidenciou o intrínseco vínculo no desenvolvimento dos processos erosivos lineares com as mais diversas formas de uso da terra e com os atributos naturais da área de estudo. Deste modo, considera-se que o procedimento metodológico adotado nesta pesquisa constitui-se em ferramenta fundamental para compreender a dinâmica dos processos erosivos lineares, possibilitando a obtenção de dados de extrema relevância para o planejamento do uso e ocupação da terra.
Evaluation of the the linear erosion processes dynamic and its relation with the evolution of the land use
Keywords: Land-use evolution; Linear erosion processes; Lito-pedologic characteristics; anthropogenic effect; erosion; human activity; land use change; land use planning; Brazil; Sao Paulo [Brazil]; South America